2-Isogenies Between Elliptic Curves in Hesse Model - Silva, João Paulo da; Dahab, Ricardo; López, Julio (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas ComputacionaisDO - 10.5753/sbseg.2018.4270, 2018)
Cryptosystems based on the problem of calculating isogenies between supersingular elliptic curves were recently proposed as strong candidates in the area of Post-Quantum Cryptography. In order to evaluate isogenies applied in cryptography constructions we use the Vèlu formula. However, this formula only applies to elliptic curves in the Weierstrass model. This paper presents morphisms that can be used to construct 2-isogeny formulas for curves in the Hesse model.